JFK [videorecording (DVD)] : like no other - Platt, Oliver; Bellows, Susan; Bellows, Susan
This film explores Kennedy's childhood years as the privileged but sickly son of one of the wealthiest men in America, his early political career as a lackluster congressman, his successful run for the U.S. Senate, and the game-changing presidential campaign that made him the youngest elected president in U.S. history.